Pulp and paper making from Acacia (Acacia Mangium) by using kraft pulping - Musa, Muhammad Faizal; Radhi, Muhammad Azizul; Mohd Yazied, Mohamad Alif; Mohd Tahir, Muhammad Rahman (2010)
This research was done on Acacia mangium from Fabaceae to study about the strength properties of paper and suitability by using chemical pulping. The method that has been used in kraft pulping. The pulp that been done produced in cooking wood chips by using rotary digester. This process are distinguish between the different alkaline active and beating to determine the maximun strength of paper. From the different, the contain in alkaline active and revolution beating that been suitable to use is 20% of AA at 20 000 rpm because it can produce the paper that have maximum strength. The paper structure, physical and mechanical like tensile strength, tearing strength and folding endurance will be tested. From the research, the tensile strength is 39.02 mNm2/g, tearing strength 0.28 mNm2/g and folding endurance 2.5 mNm2/g. From here, we can indicate that the uses of differences alkaline active and revolution of beating in paper making give significant effect properties.